PERAN SANTRIWATI DALAM PENGELOLAAN SAMPAH PERSPEKTIF STRUKTURAL FUNGSIONAL TALCOTT PARSON - Sofiyatun; Abdul Rokhim; M. Muhibbin (SOSIOEDUKASI, 2025)
This research aims to analyze the role of female students in waste management based on Talcott Parson's imperatives. This research is empirical juridical research with a juridical approach through legal studies related to the research topic and an empirical approach through sociological facts in the field. This research provides a more comprehensive picture regarding the role of female students in waste management and effective and efficient regulatory strategies in waste management. The results of this research are that the role of female students is carried out by taking concrete actions in minimizing waste, sorting waste, utilizing waste, and understanding materials in waste management in formal institutions and Islamic boarding school environments. Waste management is carried out in line with Talcott Parson’s imperative called AGIL (adaptation, goal attainment, integration and latency) with the existence of waste management activities that are intracurricular, co-curricular and extra-curricular in formal institutions and at the Islamic boarding school level.